Ecotoxicity assessment of stabilized sew sludge from municipal sewage treatment plant = Ocena ekotoksyczności ustabilizowanych osadów ściekowych pochodzących z komunalnej oczyszczalni ścieków - Włodarczyk, Elżbieta; Próba, Marta; Wolny, Lidia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Aim of this study was to evaluate the ecotoxicity of municipal sewage sludge conditioned with polyelectrolytes, taken from selected sewage treatment plant. Using the bioindication analysis overall toxicity was assessed, which allows to know the total toxicity of all the harmful substances contained in sewage sludge, in many cases acting synergistically. To prepare a sample of sludge for the basic test, all analyses were performed with a ratio of liquid to solid of 10:l (water extract), Daphnia pulex biological screening test was used.
Keywords: osady ściekowe; kondycjonowanie; ekotoksyczność; wyciągi wodne; Daphnia pulex; analiza bioindykacyjna; sewage sludge; conditioning; ecotoxicity; water extract